Accumulation of γ‐aminobutyric acid during cold storage in mulberry leaves. (29th June 2018) - Li, Erna; Luo, Xinxin; Liao, Sentai; Shen, Weizhi; Li, Qian; Liu, Fan; Zou, Yuxiao
Summary: The γ‐aminobutyric acid (GABA) contained in mulberry leaves has the effect of improving mood. Mulberry leaf cultivars 'Kangxuan 01‐28', 'Lunbai No.1' and 'BR 60' were analysed for GABA accumulation under low temperature storage. The effects of ice temperature storage (ITS), cold acclimation combined with ice‐temperature storage (CACIS) and cold storage (CS) on GABA and associated enzymes, soluble protein and leaf colour were measured. The increase in GABA content differed among varieties. Under different low temperature storage treatments, the GABA concentration increased by 33.93‐fold, 11.75‐fold and 4.28‐fold in mulberry leaves compared with the initial concentration in the three cultivars 'Kangxuan 01‐28', 'Lunbai No.1' and 'BR 60', respectively. GAD activity and soluble protein were positively correlated with GABA concentration, while GABA‐T activity showed an opposite trend to the GABA concentration. After being treated with ITS, 'Kangxuan 01‐28' could accumulate higher GABA and should be consumed within 7 days. Abstract : Under low temperature storage treatments, the GABA content of mulberry leaves increased.